2006
DOI: 10.1093/jnci/djj231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silibinin on the Growth and Progression of Primary Lung Tumors in Mice

Abstract: Silibinin inhibits lung tumor angiogenesis in an animal model and merits investigation as a chemopreventive agent for suppressing lung cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
146
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(156 citation statements)
references
References 31 publications
4
146
0
3
Order By: Relevance
“…20 Silibinin possesses strong anticancer efficacy against both carcinogen-induced primary lung tumors and chemotherapy resistant lung tumor xenografts, where it decreased tumor incidence, inhibited tumor growth and progression by downregulating inducible nitric oxide synthase and Cox-2 mediated signaling, and overcame NFκB-mediated chemoresistance, respectively. 20,22,23 Additionally, growth inhibitory and pro-apoptotic effects of silibinin were recently observed in NSCLC A549 and H1299 cells. 19,25 Mechanistically, silibinin modulated cytokines mediated signaling and induced cell cycle two regions of p21 promoter: region a: -324 to -676 and region b: Sp1/Sp3 binding site +41 to -343.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…20 Silibinin possesses strong anticancer efficacy against both carcinogen-induced primary lung tumors and chemotherapy resistant lung tumor xenografts, where it decreased tumor incidence, inhibited tumor growth and progression by downregulating inducible nitric oxide synthase and Cox-2 mediated signaling, and overcame NFκB-mediated chemoresistance, respectively. 20,22,23 Additionally, growth inhibitory and pro-apoptotic effects of silibinin were recently observed in NSCLC A549 and H1299 cells. 19,25 Mechanistically, silibinin modulated cytokines mediated signaling and induced cell cycle two regions of p21 promoter: region a: -324 to -676 and region b: Sp1/Sp3 binding site +41 to -343.…”
Section: Discussionmentioning
confidence: 97%
“…13,20,22,23 Silibinin, a flavonolignan isolated from milk thistle (Silybum marianum) seeds, is well known for its hepatoprotective activity, and is used clinically and as dietary supplement against liver toxicity for decades. 20 Silibinin possesses strong anticancer efficacy against both carcinogen-induced primary lung tumors and chemotherapy resistant lung tumor xenografts, where it decreased tumor incidence, inhibited tumor growth and progression by downregulating inducible nitric oxide synthase and Cox-2 mediated signaling, and overcame NFκB-mediated chemoresistance, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Accumulating evidence indicates that silibinin has anticancer activity in various tumor cells, including cancers of prostate (5)(6)(7)(8)(9), breast (10,11), skin (12), colon (13), lung (14), kidney (15,16), and bladder (17)(18)(19)(20). There is increasing interest in elucidating the mechanisms of action for silibinin as an effective agent for chemoprevention and chemotherapy against various types of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Silymarin possesses hepatoprotective properties and has been widely used for decades to treat patients with liver disease (8). Recent studies have shown that silibinin and silymarin inhibits growth of many cancers including breast, lung, colon, pancreas, and prostate cancer cells (9)(10)(11)(12). The anticancer efficacy of silibinin is associated with cell cycle arrest, apoptosis, and antiangiogenesis (13).…”
Section: Introductionmentioning
confidence: 99%